2000
DOI: 10.1039/b000957l
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the nonlinear optical properties of diphenyl ether and diphenyl sulfide compounds

Abstract: Fourteen diphenyl ether and diphenyl sul®de compounds were synthesized and a comparative study on their second-order nonlinear optical properties was carried out. The results showed that these two kinds of compounds all had fairly large molecular ®rst-order nonlinear optical hyperpolarizabilities b, but they have very different second harmonic generation (SHG). The diphenyl sul®de derivatives usually have strong SHG effects while almost all the diphenyl ether compounds have no SHG response, which can be attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…8,[65][66][67] Studies of the quadratic hyperpolarizability of 4-amino-4′-nitrodiphenyl chalcogeno-ethers by EFISH showed that the S, Se, and Te ethers have similar hyperpolarizabilities, higher than that of the O analogue. 68,69 The result indicates that the molecular nonlinear responses of 1 and 2 are indeed similar and it is reasonable to compare the resonant responses of the solids.…”
Section: Resultsmentioning
confidence: 74%
“…8,[65][66][67] Studies of the quadratic hyperpolarizability of 4-amino-4′-nitrodiphenyl chalcogeno-ethers by EFISH showed that the S, Se, and Te ethers have similar hyperpolarizabilities, higher than that of the O analogue. 68,69 The result indicates that the molecular nonlinear responses of 1 and 2 are indeed similar and it is reasonable to compare the resonant responses of the solids.…”
Section: Resultsmentioning
confidence: 74%
“…They have shown that all aniline derivatives bonding via a methylene bridge (−CH 2 −) exhibit SHG activity in powder form. Zhao et al 3 have synthesized several diphenyl sulphide compounds. Their results showed that diphenyl sulphide derivatives have strong SHG effects.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric Schiff bases are of great interest because of their semiconducting properties,1, 2 formation of metal chelates,3, 4 thermal stability,5 opto‐electronic properties,6 and also due to their ability in the removal of metal ions 7. Phenyl thiourea and its derivatives have also gained importance due to their good properties such as high corrosion resistance,8 in opto‐ electronics,9 and in the removal of heavy metal ions,10 and toxic elements such as mercury 11. On the basis of the aforementioned advantages of azomethine and phenyl thiourea groups, it is of interest to synthesize new generation of polymers containing these groups in the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%